Molecular Identification and Phylogenetic Trees Reconstruction of Blue Swimming Crabs (Decapoda: Portunidae) from Pangpang Bay, Banyuwangi - Sapto Andriyono; Reza Istiqomatul Hidayah; Laksmi Sulmartiwi; Andi Aliah Hidayani; Md. Jobaidul Alam (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2022)
Crabs are a group of Decapoda (Portunidae) that act as keystone species from Pangpang Bay as the marine benthic organism. Besides having an ecological function, crab also provides essential components for human health. The crab identification technique is usually conducted based on morphology and anatomy characteristics, in which certain body parts as the key for identification. This study used two identification methods, i.e. morphological features and a molecular approach. Although morphological identification has been carried out, the molecular techniques provide better accuracy and, at the same time, provide additional information about the characteristics of mitochondrial DNA. The purpose of this study is to identify the blue swimming crab caught by a traditional fisherman at Pangpang Bay, Banyuwangi, based on mitochondrial DNA sequence on cytochrome c oxidase subunit I, and reconstructed the phylogenetic tree including genetic distance also was analysed. The nucleotide sequences of the COI gene were analysed by Chromas, Clustalω, Reverse-Complement, and the MegaX. The phylogenetic tree and genetic distance calculations were carried out using Mega X software through the Neighbor-Joining (NJ) Algorithm with the addition of several sequences from the NCBI online database. This study confirmed that the specimen of Pangpang Bay is Portunus pelagicus (BWIPP001 and BWIPP003) and Portunus sanguinolentus (BWIPP002). The species of P. pelagicus have 99.99% similarities with the same species (KJ168060) from China, while the P. sanguinolentus is close to the same species (EU284144) with a per cent identity is 99.97%. The genetic distance, for P. pelagicus and P. sanguinolentus, were in range of 0.00-0.066 and 0.00-0.005 respectively.